Development Of A Five-Level Diagnostic Instrument On The Rate Of Reaction Material: To Identify The Causes Of Students' Misconceptions And Representation - Rokhim, Deni Ainur; Widarti, Hayuni Retno; Munzil, Munzil (Jurnal Inovasi Pendidikan Kimia, 2025)
This journal article aims to develop a five-level reaction diagnostic instrument. The diagnostic instrument was created by combining multiple choice questions with core questions and drawing sub microscopically and symbolically. Based on the research results, this diagnostic test is valid because empirical validation gives Rxy > Rtable at a significance level of 5%. In the reliability test, the items were declared reliable as evidenced by the Level A reliability value; the value of Cronbach's alpha coefficient was 0.707; The R level was 0.664, and that of the multiple representatives was 0.957. The reliability results show that the five-level diagnostic tool has high criteria.